The hindrances to perform the COVID-19 vaccination in Brazil - Matheus Negri Boschiero; Camila Vantini Capasso Palamim; Fernando Augusto Lima Marson (Taylor & Francis Group, 2021)
Introduction Brazil is one of the epicenters of COVID-19 pandemic and faces several hindrances to make his COVID-19 vaccination plan efficient. Methods The Brazilian COVID-19 vaccination plan was evaluated and the hindrances to make the COVID-19 vaccination plan efficient were described and discussed. Results High territorial extension might contribute to a delay on the COVID-19 vaccination, due to difficulty in delivering vaccines to furthest Brazilian states and to all the interior cities. The choice among the vaccines should be done based on the type of storage and must consider the transport conditions necessary to maintain its effectiveness. The indigenous individuals were included with health-care workers as the first group to be vaccinated, inflaming the number of vaccines doses distributed in states where the indigenous population have higher prevalence. The antivaccine movement and the politicization of the vaccine are also hindrances to be overcome in Brazil. The COVID-19 incidence or mortality rate and the distribution of intensive care units (ICUs) are not a criterion to distribute the vaccines, as we did not identify a correlation between these markers and the number of vaccines. However, a strong or very strong correlation occurred between the number of COVID-19 vaccines and the number of COVID-19 cases, deaths by COVID-19, gross domestic product, as well as populational density. A total of 83,280,475 doses of COVID-19 vaccines were distributed in Brazil. In the first dose, the Coronavac (Sinovac™), AZD1222 (AstraZeneca/Oxford™), and BNT162b (Pfizer/BioNTech™) vaccines were responsible to vaccinate, respectively, 9.61%, 6.69%, and 0.35% of the Brazilian population. In the second dose, the Coronavac, AZD1222, and BNT162b vaccines were responsible to vaccinate, respectively, 7.52%, 0.53%, and <0.01% of the Brazilian population. Conclusions The Federal Government must evaluate the hindrances and propose solutions to maximize the immunization against COVID-19 on Brazil.